2009
DOI: 10.3390/molecules14124858
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of 2,4-Disubstituted Thiazoles Using MnO2

Abstract: Structurally diverse thiazoles with electron-donating and electron-withdrawing groups were conveniently synthesized through manganese dioxide (MnO2) oxidation of the corresponding thiazolines. The effect of substitution at the 2- and 4-positions was investigated. The desired thiazoles with aryl or vinyl substitutions at the 2- or 4-position can be obtained in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Recent surveys showed that thiazole compounds play important role as antibacterial, anti-inflammatory, anticonvulsant and anticancer agents [10,11]. Structural activity relationship (SAR) study based on thiazole revealed that substituents on a particular position at position 2 and 4 of the 1,3-thiazole ring affect the biological behavior [12,13]. Other than that, molecular docking study is a computer-assisted drug design (CADD) that is used to predict eligible orientation of ligand towards specific receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys showed that thiazole compounds play important role as antibacterial, anti-inflammatory, anticonvulsant and anticancer agents [10,11]. Structural activity relationship (SAR) study based on thiazole revealed that substituents on a particular position at position 2 and 4 of the 1,3-thiazole ring affect the biological behavior [12,13]. Other than that, molecular docking study is a computer-assisted drug design (CADD) that is used to predict eligible orientation of ligand towards specific receptor.…”
Section: Introductionmentioning
confidence: 99%
“…The crude product was purified using column chromatography on silica gel G60, eluting with hexane-EtOAc (3:2) to give, as a yellowish, fluffy solid, 4-phenyl-2-styrylthiazole (4a) (0.109 g, 82.6%), mp 130-132 ºC (Lit. [39][40][41] …”
Section: Methodsmentioning
confidence: 99%
“…Molecular entities bearing thiazole ring system(s) form an important class of natural and synthetic compounds because of their physicochemical properties [ 1 , 2 , 3 , 4 ].Furthermore, they exhibit a wide range of biological activities such as cardiotonic [ 5 ], antifungal [ 6 , 7 ], analgesic [ 8 ], anticonvulsant [ 9 ], antituberculosis [ 10 ], antiviral [ 11 ], anti-inflammatory [ 12 ], anti-HIV [ 13 , 14 ], and anticancer activities [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%